2019
DOI: 10.3390/lubricants7090072
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Crystals in Tribology

Abstract: The present work intends to provide a brief account of the most recent advances in the use of ionic liquid crystals (ILCs) in the field of tribology, that is, the development of new lubricants with the ability to reduce the coefficients of friction and the wear rates of materials under sliding conditions. After a definition of ILCs and their relationship with neutral liquid crystals (LCs) and ionic liquids (ILs), the review will be focused on the influence of molecular structure and composition on the tribolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
(48 reference statements)
0
8
0
1
Order By: Relevance
“…Bei For-K schungsarbeiten, die sich mit der Untersuchung der makroskopischen Reibung beschäftigen, stehen Additive zur Optimierung von Wasser als Schmierstoff im Fokus. Dazu werden in wissenschaftlichen Arbeiten MoS2 Nanopartikel [22], CuO-beschichtete Nanopartikel [23], geschichtete Doppelhydroxid-Nanoplättchen [24], fluoriertes Graphen [25], Lithiumsalz und nichtionische Tenside [26], oxidierte aus Holz stammende Nanokohlenstoffe [27], Pflanzenextrakte [3] und ILCs [28] diskutiert. Es wurde herausgefunden, dass das Einlaufverhalten zum Erreichen extrem niedriger Reibung einen entscheidenden Einfluss bei der Verwendung einer wässrigen Mischung mit Schwefelsäure und Glycerin hat [29].…”
Section: Stand Der Wissenschaftunclassified
“…Bei For-K schungsarbeiten, die sich mit der Untersuchung der makroskopischen Reibung beschäftigen, stehen Additive zur Optimierung von Wasser als Schmierstoff im Fokus. Dazu werden in wissenschaftlichen Arbeiten MoS2 Nanopartikel [22], CuO-beschichtete Nanopartikel [23], geschichtete Doppelhydroxid-Nanoplättchen [24], fluoriertes Graphen [25], Lithiumsalz und nichtionische Tenside [26], oxidierte aus Holz stammende Nanokohlenstoffe [27], Pflanzenextrakte [3] und ILCs [28] diskutiert. Es wurde herausgefunden, dass das Einlaufverhalten zum Erreichen extrem niedriger Reibung einen entscheidenden Einfluss bei der Verwendung einer wässrigen Mischung mit Schwefelsäure und Glycerin hat [29].…”
Section: Stand Der Wissenschaftunclassified
“…Some dicationic ionic liquids (DILs) are more thermally stable than those based on monocationic units 5 , 12 . Imidazolium based DILCs have found growing applications in areas varying from biochemistry and biology 13 15 to electrochemistry 16 and electro-optics 17 to tribology 18 . Recent studies have demonstrated that dicationic ILs not only show favorable physicochemical properties 19 but are also significantly different in their dynamic behaviour 20 as compared to conventional monocationic analogs.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into complex fluids with anisotropic properties, e.g., mesogenic fluids, ionic liquids and ionic liquid crystals, have shown their potential for friction reduction [28,29]. Liquid crystals (LCs) are a further substance class of additives which have been shown to improve friction and optimize water as a lubricant.…”
Section: Introductionmentioning
confidence: 99%
“…LCs have already been intensively investigated as pure lubricants [31] and as additives in mineral oils [32,33] and water [34,35]. A new field of research is currently opening up in the field of ionic liquid crystals (ILCs) [29], also in combination with water [36,37]. It is assumed that the resulting ultralow friction and wear are ascribed to their specific molecular interactions and orientation in the shear flow [38].…”
Section: Introductionmentioning
confidence: 99%